The Level of Interest or Motivation With Differentiated Instruction in Blended Learning Among Low Achieving Students - Hoe, Sin Ling; Yeo , Kee Jiar; Mohd Kosnin, Azlina (Journal of Education for Sustainability and Diversity, 2024)
The consequences of nationwide school closures in reaction to the COVID-19 outbreak are far- reaching, affecting instruction and learning over the last two academic years. Blended learning is one of the growing educational methods in the digital era. Most teaching and learning processes have actively embraced blended learning to improve quality and keep up with technological innovation. Many children require differentiated instruction to satisfy their individual learning needs. This teaching method has the potential to greatly improve the lives of at-risk students. Teachers' attitudes and beliefs can help inspire students in a variety of ways. This study will look into how differentiated instruction in blended learning affects students' degrees of interest or motivation. To collect data from research participants among low-achieving students, the current study used a quantitative research methodology (Descriptive methodology). Data was collected from low achieving students using a set of surveys to determine their level of interest or motivation in blended learning. According to the findings of this research, teachers’ differentiated instruction on blended learning had a generally positive impact on students' levels of interest or motivation. If students are given the tools they need, they can become active participants in their own educational adventures rather than passive learners.